2011
DOI: 10.1007/s10597-011-9405-x
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison Study of Psychological, Family Function Marital and Life Satisfactions of Polygamous and Monogamous Women in Jordan

Abstract: This study surveyed a 2009 convenience sampling of 199 women, 93 of whom were first (or senior) wives in polygamous marriages and 106 were wives in monogamous marriages. We deployed the McMaster Family Assessment Device (FAD), ENRICH marital satisfaction questionnaire, SCL-90 mental health symptoms checklist, Rosenberg self-esteem (SE) scale, and Diener, Emmons, Larsen, and Griffin life satisfaction scale, a basic sociodemographic scale, including attitudes towards polygamy. Women from polygamous families expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 29 publications
3
45
0
Order By: Relevance
“…A "junior wife" is the most recent wife joining the marriage [14] . This unique family structure forces cooperation between the wives in the household chores and the fields (in rural areas), while they are subject to the husband's authority and in constant competition over his love, attention and financial resources [15,16] . Studies conducted in different countries have shown that polygamy can lead to co-wife jealousy, competition, and unequal distribution of household and emotional resources [17] , and generate acrimony between co-wives and between the children of the different wives [18] .…”
Section: Brief Articlementioning
confidence: 99%
See 1 more Smart Citation
“…A "junior wife" is the most recent wife joining the marriage [14] . This unique family structure forces cooperation between the wives in the household chores and the fields (in rural areas), while they are subject to the husband's authority and in constant competition over his love, attention and financial resources [15,16] . Studies conducted in different countries have shown that polygamy can lead to co-wife jealousy, competition, and unequal distribution of household and emotional resources [17] , and generate acrimony between co-wives and between the children of the different wives [18] .…”
Section: Brief Articlementioning
confidence: 99%
“…Studies conducted in different countries have shown that polygamy can lead to co-wife jealousy, competition, and unequal distribution of household and emotional resources [17] , and generate acrimony between co-wives and between the children of the different wives [18] . They have also shown that polygamy is associated with mental illness (in particular, depression and anxiety) among women and children [15,16] . Chaleby [14] has found a disproportionate number of women in polygamous marriages (mostly senior wives) among psychiatric outpatient and inpatient populations in Kuwait.…”
Section: Brief Articlementioning
confidence: 99%
“…Thus, while there is a vast body of research on marital satisfaction and its correlates, our knowledge regarding the dynamics that underlie marital satisfaction is primarily based on western studies. In the Gulf Arab region, however, research on this subject remains limited (Alqashan, 2008;Al-Krenawi, 2010;Al-Krenawi, Graham, & Al Gharaibeh, 2011;Al-Othman, 2012;Balderrama-Durbin et al, 2011). Thus, pertinent questions as basic as what constitutes marital satisfaction in the Gulf Arab culture, to complex ones such as what social, cultural, and psychological factors may be associated with marital satisfaction in Gulf Arab societies, remain mostly unaddressed.…”
Section: Introductionmentioning
confidence: 99%
“…Polygamy as found in this study is a recognized risk factor for psychological morbidity in children 28,29 , often polygamous families are larger and resource allocation per member is likely to be smaller. The chances that an affected child will not get enough resources for his/her care in a large family is high and may carry with it an elevated risk of poor asthma control and psychological morbidity.…”
Section: Discussionmentioning
confidence: 54%